Fabrication and mechanism of a novel direct solid-state Z-scheme photocatalyst CdS/BiOI under visible light. Issue 40 (26th September 2016) - Song, Chengjie; Feng, Yi; Shi, Weidong; Liu, Chunbo
Abstract : A direct CdS/BiOI Z -scheme heterojunction has been successfully synthesized via a hydrothermal method for the first time. Abstract : A direct CdS/BiOI Z -scheme heterojunction has been successfully synthesized via a hydrothermal method for the first time. The photocatalytic performances of as-prepared samples were evaluated by rhodamine B degradation under visible light ( λ > 420 nm) irradiation. The phase structures, morphologies and optical properties of the obtained samples were investigated by several characterization tools such as XRD, SEM, TEM, HRTEM, STEM, XPS, and UV-vis, photocurrent and PL spectroscopy. The results revealed that the CdS/BiOI Z -scheme heterojunction exhibited much higher photocatalytic activity than pure BiOI and CdS, and the sample of CdS/BiOI-2 showed the best activity among all the heterostructure photocatalysts. In addition, the ESR spectrum indicated that ˙O2 − and e − were the main active species for the photocatalytic degradation of RhB in our experiment.